Evaluation of amylase immobilization on nanoclay by size exclusion chromatography and its application for starch removal from plant extracts of herbal medicines. (February 2021) - Shakerian, Farid; Zhao, Jing; Li, Shao-Ping
Graphical abstract: Highlights: Immobilization of amylase on modified montmorillonite clay. Starch removal by immobilized amylase prior to herbal glycoanalysis. Immobilized amylase has advantages of reuse and easy separation from substrate. Evaluation of enzyme immobilization by size exclusion chromatography. Abstract: A simple method for immobilization of amylase (Am) on montmorillonite (Mt) was developed. Direct immobilization of crude commercial Am was initially evaluated by size exclusion chromatography by considering Am peaks (in comparison to the pure enzyme from the same source), while the immobilized enzyme performance was monitored by anion exchange chromatography. The immobilized Am showed approximately 55.6 ± 0.7 % (n = 3) of the activity of the free enzyme. Both free and immobilized Am showed maximum performance in neutral pH (pH ∼ 7). The immobilized Am maintained more than 60 % of its initial activity after 10 reuse cycles. The immobilized enzyme was successfully applied for starch removal in crude carbohydrates extracted from medicinal plant samples.